Limiting behaviour of the oscillatory system with the presence of random disturbances of parameters of this system. II - Skorokhod, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
The asymptotic behavior is studied of the solution of a second-order linear system in the presence of random perturbations represented by an ergodic Markov process with a finite state space. The case is investigated when the averaged system describes a simple harmonic oscillation.